Polypharmacy in Older Adults with Cancer - Maggiore, Ronald J. (AlphaMed Press, 2010)
The definition of “polypharmacy” ranges from the use of a large number of medications; the use of potentially inappropriate medications, which can increase the risk for adverse drug events; medication underuse despite instructions to the contrary; and medication duplication. Older adults are particularly at risk because they often present with several medical conditions requiring pharmacotherapy. Cancer-related therapy adds to this risk in older adults, but few studies have been conducted in this patient population. In this review, we outline the adverse outcomes associated with polypharmacy and present polypharmacy definitions offered by the geriatrics literature. We also examine the strengths and weaknesses of these definitions and explore the relationships among these definitions and what is known about the prevalence and impact of polypharmacy.